Fetal Tracheal Occlusion for Severe Pulmonary Hypoplasia in Isolated Congenital Diaphragmatic Hernia: A Systematic Review and Meta-analysis of Survival. Issue 6 (December 2016) - Al-Maary, Jamila; Eastwood, Mary P.; Russo, Francesca Maria; Deprest, Jan A.; Keijzer, Richard
Abstract : Objective: To evaluate fetal survival after tracheal occlusion in fetuses with severe pulmonary hypoplasia and isolated congenital diaphragmatic hernia (CDH). Background: Despite recent advances in neonatal intensive care, CDH still has a high mortality and morbidity. Fetoscopic endoluminal tracheal occlusion (FETO) stimulates lung growth and improves gas exchange in animal models of CDH, but the effects in humans are still under investigation. Methods: We searched Pubmed, Cochrane, EMBASE, and Scopus databases for clinical studies on tracheal occlusion and CDH. All studies comparing FETO and a contemporary control group were included. The primary outcome was survival, with the need for oxygen on discharge the secondary outcome. Meta-analysis of outcome measures was performed and odds ratios, relative risk ratios, and 95% confidence intervals were estimated with a fixed-effects model and were reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidance. Results: Between 1997 and 2015, five eligible studies describing 211 patients were included (101 control and 110 FETO). All studies selected isolated severe CDH fetuses with a lung-to-head ratio 1.0 or less and liver herniation into the thoracic cavity. FETO favored survival outcome (odds ratio 13.32; 95% confidence interval, 5.40–32.87). Meta-analysis of the secondary outcome oxygen need at discharge could not be calculated, because it was not reported in all included studies. Conclusions: FETO improves survival in isolated CDH with severe pulmonary hypoplasia compared with the standard perinatal management.